Realistic experimental heat transfer characteristics of radiant floor heating using sidewalls as heat sinks - Acikgoz, Ozgen; Karakoyun, Yakup; Yumurtaci, Zehra; Dukhan, Nihad; Dalkilic, Ahmet Selim (ELSEVIER SCIENCE SA, 2019)
Apart from most of the relevant literature, case studies are conducted by generating a number of configurations using sidewalls as heat sinks to simulate winter conditions. These configurations correspond to distinct heat loss rates and means from a living environment, heated by an underfloor heating system. In this study, heat transfer characteristics of an underfloor heating system in a test chamber have been experimentally determined, while chilled water flows through circuits in sidewalls arranged at four different configurations. Simultaneously, supply water temperatures ranging from 30 degrees C to 45 degrees C, and a flow rate of 0.09 kg/s are applied. As a result, when the supply water temperature is 35 degrees C, with increasing number of cooled sidewalls, at configuration 2, 3, and 4 as increasing heat loss sources, total heat fluxes from the floor are found 66.36 W/m(2), 81.79 W/m(2), and 85.19 W/m(2), respectively. Correlations for the convective heat transfer coefficient and total heat flux are derived and average error rates of +/- 11% and +/- 4.5% are obtained, as 87.5% and 94% of measured data remain in +/- 30% and +/- 10% error bands considering the derived empirical correlations, respectively. Measured and calculated data are given for other researchers to validate their models. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Natural convection; Enclosure; Radiant heating; Floor heating; Energy saving; TRANSFER COEFFICIENTS; THERMAL PERFORMANCE; SYSTEMS; PUMP; WALL; CONVECTION; Construction & Building Technology; Energy & Fuels; Engineering